2022
DOI: 10.1039/d1ra08059h
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of insoluble fibrous collagen for characterization and crosslinking with phenolic compounds from pomegranate byproducts for leather tanning applications

Abstract: Green strategy for collagen and polyphenolic compound extraction. Fruitful combination of collagen-polyphenols via crosslinking with high compatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…On the other hand, the tannic acid elution profile illustrated a self-polymerization in time showing a slow elution within Sephadex gel beads, translated by the small size of molecules. For that reason, it is worth noting that extracts obtained from L1, L2, L3, L4, I1, and I2 all have high molecular sizes of condensed tannins, which could be valued as potential agents in environmental applications [18]. Comparing elution profiles in Figure 5, it can be concluded that the different rinds varieties highlight, qualitatively and quantitatively, differences in molecular distributions of tannins content.…”
Section: Steric Exclusion Chromatography (Sec) Analysis Of Pr Varietiesmentioning
confidence: 94%
See 3 more Smart Citations
“…On the other hand, the tannic acid elution profile illustrated a self-polymerization in time showing a slow elution within Sephadex gel beads, translated by the small size of molecules. For that reason, it is worth noting that extracts obtained from L1, L2, L3, L4, I1, and I2 all have high molecular sizes of condensed tannins, which could be valued as potential agents in environmental applications [18]. Comparing elution profiles in Figure 5, it can be concluded that the different rinds varieties highlight, qualitatively and quantitatively, differences in molecular distributions of tannins content.…”
Section: Steric Exclusion Chromatography (Sec) Analysis Of Pr Varietiesmentioning
confidence: 94%
“…Indeed, catechin contains a flavon-3-ol structure (Figure 7). It has been reported previously as a condensed tannin precursor (Figure 8); these latter are polymerized products of flavanols and they are also referred to as proanthocyanidins [54] The high concentration of catechin contained in our PR varieties (especially the local varieties L1 and L4) confers to this vegetable biomass specific properties in biomaterials stabilization [18,54].…”
Section: High-performance Liquid Chromatography With a Diode-array De...mentioning
confidence: 95%
See 2 more Smart Citations
“…Total antioxidant capacity (TAC) of plant extracts and sprouts were evaluated by the Prieto et al phosphomolybdenum microspectrophotometric modified method [46]. This technique is based on the formation of a blue/Mo (V) phosphate complex at acidic pH by reducing molybdenum Mo (VI) to Mo (V).…”
Section: Total Antioxidant Capacity (Tac)mentioning
confidence: 99%